Pola Pengelolaan Penampung Air Hujan (PAH) Berbasis Modal Sosial (Studi Kasus di Pulau Ende dan Pulau Solor Provinsi Nusa Tenggara Timur) - K, FX Hermawan (Jurnal Sosial Ekonomi Pekerjaan Umum, 2014)
TDiKKiculty to gain clean water is a daily matters in the small islands of East Nusa Tenggara Province. Various eKKort to provide water supply infratructure such as rain water reservoir grant basis have been done by government, Regional Government or other parties. However, the problems does not realy solved because the approach does not fit with the social community social structure and their capital. This study aimed to find a proper relief pattern suitably with the social capital owned by the community. Ende and Solor Islands of East Nusa Tenggara Province has been chosen as a case study location. The study methods is a quantitative with multiple linear regression using dummy location variable and aid pattern supported by a qualitative descriptive analysis. Study result showed that the communal character aid pattern (Solor Island) will binds more social capital, meanwhile the individual character aid pattern (Ende Island) will estrange social capital.